The Influence of Quantity Surveyor Competence on Construction Project Success in Bali Province - Eka Marawitari; A. A.Gde Agung Yana; Anak Agung Diah Parami Dewi (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
The success of a construction project is closely linked to the project's ability to meet its cost and schedule targets. In private-sector building projects in Bali Province, cost deviations and schedule delays remain common, particularly in villa, hotel, resort, and similar commercial developments. Quantity Surveyors (QS) play an important role in cost control through quantity measurement, cost estimating, the preparation of Bills of Quantities, contract administration, progress valuation, variation order management, cost reporting, and final account preparation. This study examines how the competence of Quantity Surveyors contributes to construction project success, particularly in relation to cost and time performance. It also investigates whether human resource management (HRM) can strengthen the relationship between QS competence and project outcomes. A quantitative method was employed, with data analysed through Structural Equation Modelling–Partial Least Squares (SEM-PLS). The instrument was validated using the Content Validity Index (CVI), tested through a pilot study, and subsequently used for the main data collection involving 103 respondents. The findings show that QS competence has a positive and significant effect on project success. However, HRM was not found to moderate the relationship between QS competence and project success. These findings indicate that both QS competence and HRM independently support project success, but that HRM is more appropriately understood as a direct influencing factor rather than as a moderating variable.